2017
DOI: 10.3141/2606-02
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Factors to Increase the Public's Acceptability of Road-Pricing Schemes

Abstract: User acceptability has become a critical issue for the successful implementation of transport pricing measures and policies. Although several studies have addressed the public acceptability of road pricing, little evidence can be found of the effects of pricing strategies. The acceptability of alternative schemes for a toll network already in operation is an issue to be tackled. This paper contributes to the limited literature in this field by exploring perceptions toward road-pricing schemes among toll road u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
3
13
1
Order By: Relevance
“…The second group covers different trip-related attributes such as type of vehicle, trip purpose, or trip frequency. Finally, the third group comprises attitudinal variables specific to individuals, such as their previous awareness on electronic toll collection systems, their perceptions and beliefs towards toll rates and time savings provided by toll facilities, or their personal benefits from the toll policy (Bueno et al 2017). The questionnaire collected information from individuals covering this three groups of variable (see Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second group covers different trip-related attributes such as type of vehicle, trip purpose, or trip frequency. Finally, the third group comprises attitudinal variables specific to individuals, such as their previous awareness on electronic toll collection systems, their perceptions and beliefs towards toll rates and time savings provided by toll facilities, or their personal benefits from the toll policy (Bueno et al 2017). The questionnaire collected information from individuals covering this three groups of variable (see Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the survey collected further variables regarding users' willingness to pay in interurban toll roads (Gomez et al 2015) and users' acceptability towards different road pricing schemes (Bueno et al 2017). The research also considers further aspects which may influence users' attitudes such as unitary toll rates applied and the type of tolled infrastructure (tunnel/interurban section).…”
Section: Methodsmentioning
confidence: 99%
“…The key factors affecting the MAP values for DB and TB road pricing were users' income and frequency of motorway usage, with those with higher income being more willing to pay and more frequent users being less willing to pay, similar to conclusions from Yusuf et al (2014). Contrary to some previous studies that concluded that income does not influence WTP or acceptability (Bueno et al 2017;Gomez et al 2017;Jaensirisak et al 2005), one must take into account the fact that users in North Macedonia might be poor in both time and money. Thus, income can have a significant effect on the very capacity to afford road pricing for certain social groups.…”
Section: Discussion Of Resultsmentioning
confidence: 49%
“…Despite the wide range of literature on user perspectives, most of the previous literature focuses on only one motorway pricing scheme without accounting for differences between schemes (Jaensirisak et al 2005;Bueno et al 2017;Jou et al 2012). In general, research has shown that more complex road pricing schemes are likely to be less acceptable (Bonsall et al 2007;Vrtic et al 2007;Zmud and Arce 2008).…”
Section: Background Of User Perspectives On Road Pricingmentioning
confidence: 99%
See 1 more Smart Citation